Trazodone: A New Antiepileptic Drug for Dravet Syndrome? - Azevedo Kauppila, Linda; Amorim, Isabel; Bentes, Carla; Peralta, Ana Rita (International Journal of Epilepsy, 2018)
Dravet syndrome (DS) is associated with severely refractory seizures. Recent studies suggest possible antiepileptic effects of serotonergic drugs. We report the case of a 25-year-old woman with DS-related epilepsy (SCN1A mutation), with daily seizures since childhood, associated with developmental delay. Several antiepileptic drug regimens were tested, without clear benefit. Over the years, she maintained a pattern of diurnal and nocturnal seizures, with a nocturnal predominance averaging two tonic–clonic seizures per night, with periods of seizure clusters. On routine electroencephalography (EEG), frequent, subtle myoclonic seizures during sleep were detected. A seizure-free period or significant reduction in seizure frequency was never attained. Trazodone was started due to insomnia. This led to a remarkable as well as long-standing clinical and neurophysiological improvement: less than one reported tonic–clonic seizure per month during the next 18 months, reduction in interictal epileptiform activity (170/h vs. 30/h of sleep), myoclonic seizures (90/h vs. 0.7/h of sleep), and tonic–clonic seizures (2/night to 0) on video-EEG. Serotonergic pathway modulation effects on DS-related epilepsy were observed in animal studies, in addition to small case series using lorcaserin and fenfluramine. To the best of our knowledge, no clinical data exist showing that trazodone may be an efficacious agent in patients with DS. Despite limitation of an isolated case with possible chance factors, our data, given the striking effect, provide this clinical evidence for the first time, and may have important clinical implications in patients with DS, reinforcing the need for further research on this subject.
Keywords: Dravet syndrome; serotonergic pathways; trazodone